Study of silver nanoparticle effects on some molecular responses and metabolic pathways of Phytophthora parasitica - Shaheen Bibi; Jose C Huguet-Tapia; Zunaira Afzal Naveed; Ashraf SA El-Sayed; Sujan Timilsina; Jeffrey B Jones; Gul Shad Ali (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2021)
Phytophthora parasitica is a devastating plant pathogen that has a wide host range. As a new approach, silver nanoparticles (AgNPs) were assessed to control it. Previously AgNPs were shown to inhibit mycelial growth, zoospore production and germination, and germ tube elongation. However, the mechanism(s) of bioactivity of AgNPs on changes in metabolic patterns in P. parasitica has not been completely resolved. P. parasitica was exposed to AgNPs at several time points, RNA-Sequences were extracted, and then selected key genes in several of the pathways were verified for the level of expression using qRT-PCR. For RNA-Seq, the reads were mapped to the P. parasitica genome INRA 310.3. Principle component analysis illustrated low variation among biological replicates and emphasized the reproducibility of results. In this paper, seven candidate genes identified by RNA-Seq were evaluated for their expression using qRT-PCR. Interestingly, qRT-PCR confirmed that the genes that were significantly altered were found to be involved in major cellular pathways such as glutathione metabolism and ribosome biogenesis. qRT-PCR also revealed heat shock protein, ABC transporter, and Glutathione-S-Transferase (GST) genes were significantly affected. These genes are related to oxidative stress. Expression of GST and heat-shock protein significantly increased at 1 hr post-exposure to AgNPs, indicating a rapid response. The analysis based on qRT-PCR makes it evident that key genes involved in many major pathways were significantly altered on exposure to AgNPs.